A taxonomic revision of the Capparis spinosa group (Capparaceae) from eastern Africa to Oceania - Fici, Silvio (Phytotaxa, 2015)
The variability, autecology and distribution of the Capparis spinosa group have been studied in eastern Africa, Madagascar, southern Asia, Australia and Oceania. In these areas the taxonomic treatment of the group, also represented in holoarctic Regions of the Old World, is still critical. The forms widespread in the study area are here referred to four subspecies of C. spinosa. The recognized subspecies mostly show geographical vicariance, except in some contact areas of the Middle East and western Himalaya. Two nomenclatural novelties, i. e. C. spinosa subsp. cordifolia comb. et stat. nov. and C. spinosa subsp. himalayensis stat. nov., are proposed. Among the recognized taxa, C. spinosa subsp. cartilaginea shows a wide distribution range including eastern Africa, Madagascar, south-western Asia to Pakistan and India, C. spinosa subsp. cordifolia is widespread in the Pacific from Indonesia eastwards to Pitcairn Islands and Hawaii, C. spinosa subsp. nummularia is recorded from western, central and northern Australia, C. spinosa subsp. himalayensis is known from Pakistan, India and Nepal.